(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
A traditional library refers to the collection of books, manuscripts, journals and other sources of recorded information. The main aim of library is to give satisfaction to the library users provided with various reference documents. However, it has certain limitations. Due to the limited number of books, limited funds and space in a particular library, resources are limited and is not sufficient for every users. Therefore, INTERNET can be an alternative source for resource collection. With the improvement in information technology, libraries also expanded and provide the resources online.